The Role of Entrepreneurial Leadership in Strengthening the Influence of Religiosity on Employee Performance - Setiawan, Ainur Rahim; Khalilah Daud Isaac Makhmut; Solikhin, Muhamad; Widjaja, Ratna A Marhaenita; Selan, Sarlotha; Adianto, Shochib (Universitas Kristen Cipta Wacana, 2024)
This study discusses the influence of religiosity on employee performance, considering the role of entrepreneurial leadership as a mediating variable. In the modern era, the development of technology and health systems increasingly impacts the quality of hospital services, which depend on the performance of human resources. One factor that can influence employee performance is religiosity, which is believed to enhance positive work behavior and quality service. However, the results of studies related to the connection between religiosity and employee performance are still inconsistent, with some showing significant effects and others showing no significant effects. In this article, entrepreneurial leadership is viewed as a factor that can strengthen the influence of religiosity on employee performance. This type of leadership emphasizes innovative decision-making, employee empowerment, and the development of organizational cultures that support high performance. Using the Structural Equation Modeling (SEM) approach, this study is expected to provide further understanding of how religiosity and entrepreneurial leadership are interrelated and influence employee performance, particularly in the healthcare sector. The findings of this study are expected to contribute to human resource management in hospitals and other sectors that require performance improvement through the management of religious values and innovative leadership.